Intercept analysis with threshold-based diversity reception for cognitive network. (22nd August 2022) - Chopra, Khyati
In this study, we have investigated the threshold-based intercept performance of decode-and-forward (DF) underlay cognitive network. The secondary users have been restricted by primary users due to interference curtailment. It has been presupposed that the secondary relays are inadequate to do correct decoding always. Therefore, only when the predetermined threshold value is realised by the relays, they can propitiously decode the message. We have explored the worst case scenario where diversity reception schemes have been applied only at the eavesdropper or adversary. Asymptotic and diversity analysis are conferred in our study for both the balanced and the unbalanced cognitive system. It has been extensively manifested that how factors like eavesdropper link quality, predetermined threshold and interference power restrictions affect intercept performance of cognitive system. Also, it is graphically demonstrated that intercept performance is enhanced by utilising the optimal relay selection scheme (OS) with surge in the number of relays.